Penerapan Prinsip-Prinsip Good Governance dalam Meningkatkan Pelayanan Publik di Kantor Kecamatan Marioriwawo Kabupaten Soppeng - Andi Baso Mappaoddang; Amir Muhiddin; Ansyari Mone (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2025)
The problems in this research are (i) how to apply the principles of good governance in improving public services in the Marioriwawo District Office, Soppeng Regency; and (ii) what factors are the obstacles to the application of the principles of good governance in improving public services at the Marioriwawo District Office, Soppeng Regency. The research method used was a survey in accordance with the research objectives. While the data collection technique is done by interviewing, or interviewing, observing, or observing which is arranged based on research variables and then answered by the selected informants in this study. Then the data collected is analyzed in inductive and deductive forms. Besides that, the author also reviews various relevant books.